2019
DOI: 10.3390/app9224744
|View full text |Cite
|
Sign up to set email alerts
|

Shear Rate-Dependent Rheological Properties of Mine Tailings: Determination of Dynamic and Static Yield Stresses

Abstract: In this paper, shear rate-dependent rheological properties of mine tailings taken from abandoned mine deposits prone to mass movements are examined using a commercial ball-measuring rheological system. The yield stresses (i.e., dynamic and static yield stresses) and viscosity of sand-rich materials are examined by the shear rate-controlled flow curve and time-dependent stress growth methods. Before yielding, the shear stress reaches a peak value (i.e., yield stress) observed for all flow curves. In the steady-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 32 publications
5
20
0
Order By: Relevance
“…It is shown that 1,2-vinyl-rich chain groups (Group A) and 1,4-trans-rich chain groups (Group B) flow under rotational shear with increasing shear rate. A wall slip is suggested to be occurred and divides area into 2 regions as also reported by Jeong et al (Jeong, 2019). Two regions are dark grey (Area 1) and light grey (Area 2).…”
Section: Results and Analysissupporting
confidence: 55%
See 1 more Smart Citation
“…It is shown that 1,2-vinyl-rich chain groups (Group A) and 1,4-trans-rich chain groups (Group B) flow under rotational shear with increasing shear rate. A wall slip is suggested to be occurred and divides area into 2 regions as also reported by Jeong et al (Jeong, 2019). Two regions are dark grey (Area 1) and light grey (Area 2).…”
Section: Results and Analysissupporting
confidence: 55%
“…The property is identical with HTPB. The behavior is also reported for paint, sand-rich material, kernel oil and coconut oil (Adewale, et al, 2017), (Green, 2004), (Jeong, 2019). Those liquids have hydrocarbon chains similar with HTPB.…”
Section: Results and Analysismentioning
confidence: 56%
“…The measurement of shear stress depends on the applied initial shear rate, as it is evident in Figure 11 comparing the F22 and F23 tests. The viscous plateau occurs (see Figure 12) independently on the initial applied shear rate (i.e., runs F22, F23 and F24) as it was already observed by Jeon [25], but it disappears as a consequence of aging due to a prolonged resting period.…”
Section: Resultsmentioning
confidence: 51%
“…The reconstituted debris-flow mixtures at different solid concentrations show a yield stress fluid behavior, characterized by the presence of a static and dynamic yield stress associated with flow starting and stopping [19,24,25]. Recently Quian et al [26] showed they are related to the microstructural material state, whereas Barnes and Walters [27] already pointed out the time dependent property of yield stress.…”
Section: Resultsmentioning
confidence: 99%
“…This further implies that the O3 formulation with greater thixotropy can provide a better-sustained release of PV, easy application at the buccal mucosal surface, as well as an enhanced retention of the gel in the buccal mucosal surface (Lee et al, 2009). The plots for both shear rate and shear stress on logarithmic scales in Figure 5 provide a better delineation of the individual flow curves for further comparison (Jeong, 2019). Specifically, Farrow's constant for the samples was determined from the slope of these plots.…”
Section: Rheological Evaluation Of the Pv-lo Sneddsloaded Chitosan Oral Hydrogelmentioning
confidence: 98%